Tingkat Efektivitas Program Yuk Jaim pada Remaja Putri di Kota Tangerang Tahun 2025 - Shafa Anidia Saharani Pakpahan; Hendra Try Ardianto (Journal of Politic and Government Studies, 2026)
Anemia in adolescent girls remains a public health problem that has the potential to impact the quality of human resources in the future. As a mitigation effort, the Tangerang City Government implemented the Yuk Jaim Program, which focuses on nutrition education and consumption of Iron Tablets (TTD). This study aims to measure the effectiveness of the Yuk Jaim Program among adolescent girls in Tangerang City in 2025. This study used a descriptive quantitative method. Data were collected through a questionnaire compiled based on program effectiveness indicators, including program understanding, target accuracy, implementation timeliness, goal achievement, and tangible changes. Data analysis was conducted univariate using frequency distribution and median values to measure the level of program effectiveness. The results showed that the Yuk Jaim Program was generally categorized as effective, characterized by relatively good indicator achievement, especially in the aspects of program understanding and target accuracy. However, there were still variations in achievement in several indicators, indicating that program implementation was not fully optimal in all aspects. This study concluded that the Yuk Jaim Program has been quite effective in its implementation among adolescent girls in Tangerang City. Although this study did not directly measure the impact on anemia prevalence, the level of effectiveness achieved indicates the program's potential contribution to supporting anemia control efforts, particularly through increased understanding and changes in health behavior.